2006
DOI: 10.3133/cir1292
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds in the nation's ground water and drinking-water supply wells

Abstract: High quality water is more than the dream of the conservationists, more than a political slogan; high quality water, in the right quantity at the right place at the right time, is essential to health, recreation, and economic growth."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 45 publications
3
105
0
3
Order By: Relevance
“…Land use was classified using an “enhanced” version of the satellite‐derived (30‐m pixel resolution), nationwide USGS National Land Cover Dataset (Vogelmann et al 2001; Price et al 2003). This dataset has been used in previous national and regional studies relating land use to water quality (Gilliom et al 2006; Zogorski et al 2006). The data represent land use during approximately the early 1990s.…”
Section: Methodsmentioning
confidence: 99%
“…Land use was classified using an “enhanced” version of the satellite‐derived (30‐m pixel resolution), nationwide USGS National Land Cover Dataset (Vogelmann et al 2001; Price et al 2003). This dataset has been used in previous national and regional studies relating land use to water quality (Gilliom et al 2006; Zogorski et al 2006). The data represent land use during approximately the early 1990s.…”
Section: Methodsmentioning
confidence: 99%
“…Many of these xenobiotic compounds interact with plants because the physical and chemical properties of the compounds impart solubility in water and, therefore, the compounds move readily through the hydrologic cycle-for example, chloroform is the most frequently detected volatile organic compound in ambient groundwater (Zogorski et al 2006). Such chemicals are derived synthetically, such as the chlorinated insecticide dichlorodiphenyltrichloroethane (DDT), or as a consequence of other processes such as the production of chloroform during water purification, and often have no natural source.…”
Section: Albert Einsteinmentioning
confidence: 99%
“…Assessments of the shallow groundwater resources of the United States by the USGS as part of the National Water-Quality Assessment Program (NAWQA) have revealed that the most commonly detected volatile organic compound in shallow, ambient groundwater is chloroform, also known as trichloromethane (Zogorski et al 2006). Chloroform detection in groundwater is attributed to the recharge of previously chlorinated drinking or waste water.…”
Section: Allelopathy and Plant-chemical Warfarementioning
confidence: 99%
“…The occurrence of VOCs in aquifers provides important water‐quality information because of the widespread, large, and increasing use of ground water for drinking water (Zogorski et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the NAWQA Program released updated findings and conclusions from the assessment of VOCs in ground water and drinking‐water supply wells. The scope of the assessment, salient occurrence findings, and detailed information for the more frequently detected VOCs are described in USGS Circular 1292 (Zogorski et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%